New dengue virus inhibitors targeting NS3-NS5 interaction identified by in silico screening - Nannetti, Giulio; Mercorelli, Beatrice; Bazzacco, Alessandro; Santi, Nicolò; Celegato, Marta; Ferla, Salvatore; Sturlese, Mattia; Buurma, Niklaas J.; Brancale, Andrea; Loregian, Arianna (Frontiers in Microbiology, 2025)
Dengue virus (DENV) poses a major public health concern as it is responsible for approximately 100 million human infections annually. Since no antiviral drugs are currently available to treat DENV infection, the development of effective therapeutic strategies is urgently needed. For anti-DENV drug discovery, the interaction between DENV NS3 and NS5 proteins represents an attractive target, as it is essential for viral replication and is highly conserved across all DENV serotypes. In this study, we report two distinct virtual screenings of commercially available drug-like compounds, which were performed to identify inhibitors of the NS3-NS5 interaction. Both screening approaches led to the identification of hit compounds that were able to reduce NS3-NS5 binding in vitro in a dose-dependent manner, as measured by an ELISA-based assay. Moreover, the hits inhibited the replication of DENV-2 at low micromolar and non-cytotoxic concentrations. Among these, hit 3 exhibited the highest selectivity index and showed antiviral activity against all four DENV serotypes. Biophysical studies indicated that hit 3 exerts its antiviral activity by directly binding to NS5. Hit 3 was then selected for structure-activity relationship studies, leading to the identification of structural analogues that retained anti-DENV activity through the disruption of NS3-NS5 interaction. Overall, this study reports the identification of a series of novel chemical scaffolds endowed with pan-dengue antiviral activity, representing a promising foundation for the development of new anti-DENV agents.